2019
DOI: 10.1002/art.40835
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Mechanical Joint Loading as an Alternative Model for Osteoarthritic Pain

Abstract: Objective Mechanisms responsible for osteoarthritic (OA) pain remain poorly understood, and current analgesic therapies are often insufficient. This study was undertaken to characterize and pharmacologically test the pain phenotype of a noninvasive mechanical joint loading model of OA, thus providing an alternative murine model for OA pain. Methods The right knees of 12‐week‐old male C57BL/6 mice were loaded at 9N or 11N (40 cycles, 3 times per week for 2 weeks). Behavioral measurements of limb disuse and mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 49 publications
5
20
0
Order By: Relevance
“…The bipedal walking model is induced by obligatory bipedal exercise, and pathogenic changes in this model are consistent with the pathology observed in humans [22]. The mechanical joint loading model is induced through vertically compressive loading on the knee and ankle joints, which shows a pathogenesis similar to human OA [44]. The STR/ort mouse develops spontaneous OA at a young age [45], whereas other mouse strains are relatively resistant to the spontaneous development of OA [46].…”
Section: Pain In Clinical Oasupporting
confidence: 67%
See 1 more Smart Citation
“…The bipedal walking model is induced by obligatory bipedal exercise, and pathogenic changes in this model are consistent with the pathology observed in humans [22]. The mechanical joint loading model is induced through vertically compressive loading on the knee and ankle joints, which shows a pathogenesis similar to human OA [44]. The STR/ort mouse develops spontaneous OA at a young age [45], whereas other mouse strains are relatively resistant to the spontaneous development of OA [46].…”
Section: Pain In Clinical Oasupporting
confidence: 67%
“…This is reminiscent of human OA, in which pain does not develop, despite advanced joint damage. On the other hand, mechanical joint loading-induced OA animals develop a robust pain phenotype, except for thermal hyperalgesia [44]. Table 1 briefly summarizes the pathology and pain behaviors reported in OA models [38,.…”
Section: Behavioral Tests To Assess Pain In Oa Animal Modelsmentioning
confidence: 99%
“…In previous work, we showed that the mechanical joint loading model at 9N induces a progressive and chronic pain phenotype from two weeks post-loading, characterized by the development of ipsilateral mechanical hypersensitivity, altered weight bearing and reduced mobility, without affecting thermal sensitivity [20]. Here, we used this model to gain insight into how the development of OA pathology in different tissues relates to the development of MJL-induced allodynia [20].…”
Section: Introductionmentioning
confidence: 99%
“…66 However, consistent with induction of PTOA, repetitive injury caused altered hindlimb weightbearing and reduced mobility; furthermore, pain-related behavior, particularly mechanical sensitization, was correlated with progression of tibiofemoral cartilage damage. 65,66 One hypothesized driver of this association is the accompanying neurovascularization of the osteochondral junction, a feature observed in osteoarthritic joints. 61 Osteoclast activity is one aspect of this process, with a recent mouse study demonstrating reduced joint innervation and pain responses when subchondral bone remodeling was inhibited.…”
Section: Discussionmentioning
confidence: 99%